Clinical, Laboratory, and Electrocardiographic Findings in Colchicine Toxicity: 10 Years of Experience - Sheibani, Mehdi; Zamani, Nasim; Gerami, Amir Hushang; Akhondi, Hossein; Hassanian-Moghaddam, Hossein (Frontiers in Medicine, 2022)
Background: We aimed to investigate the clinical, laboratory, and electrocardiographic (ECG) findings of colchicine poisoning and to evaluate if there is a correlation between them and the two major outcomes of this toxicity which are respiratory/cardiovascular failure and death. Materials and Methods: Medical records of 34 colchicine-intoxicated patients that were treated in our center during the past 10 years were retrospectively evaluated. The patient’s clinical presentation, vital signs, laboratory tests, ECGs, and outcomes were reviewed. Results: Abdominal pain, and hypotension at presentation had significant correlation with mortality (p=0.003, OR: 2.2 [4.1, 7.9], p= 0.029, OR: 13.0 [1.5, 111.8]). Mortality significantly occurred in those with sinus tachycardia, hypokalemia, metabolic acidosis, and impaired liver and kidney function tests (p-values=0.025, 0.007, 0.04, and 0.008, respectively). All the patients had some ECG abnormalities. Most frequent ECG abnormalities were pathologic ST segment elevation and depression (70%), left atrial enlargement (48%), and sinus tachycardia (37%), PR elevation in aVR lead (37%), and T wave inversion (37%). Conclusions: Colchicine toxicity is a dangerous entity regarding the cardiovascular events and requires close general and cardiac monitoring.